Effect of a Ketohexokinase Inhibitor (PF‐06835919) on In Vivo OATP1B Activity: Integrative Risk Assessment Using Endogenous Biomarker and a Probe Drug. Issue 3 (9th May 2022) - Tess, David A.; Kimoto, Emi; King‐Ahmad, Amanda; Vourvahis, Manoli; Rodrigues, A. David; Bergman, Arthur; Qui, Ruolun; Somayaji, Veena; Weng, Yan; Fonseca, Kari R.; Litchfield, John; Varma, Manthena V. S.
Abstract : PF‐06835919 is a first‐in‐class ketohexokinase inhibitor (KHKi), recently under development for the treatment of metabolic and fatty liver diseases, which inhibited organic anion transporting polypeptide (OATP)1B1 in vitro and presented drug–drug interaction (DDI) risk. This study aims to investigate the dose‐dependent effect of KHKi on OATP1B in vivo activity. We performed an open‐label study comparing pharmacokinetics of atorvastatin (OATP1B probe) dosed alone (20 mg single dose) and coadministered with two dose strengths of KHKi (50 and 280 mg once daily) in 12 healthy participants. Additionally, changes in exposure of coproporphyrin‐I (CP‐I), an endogenous biomarker for OATP1B, were assessed in the atorvastatin study (1.12‐fold and 1.49‐fold increase in area under the plasma concentration‐time profile (AUC) with once‐daily 50 and 280 mg, respectively), and a separate single oral dose study of KHKi alone (100–600 mg, n  = 6 healthy participants; up to a 1.80‐fold increase in AUC). Geometric mean ratios (90% confidence interval) of atorvastatin AUC following 50 and 280 mg KHKi were 1.14 (1.00–1.30) and 1.54 (1.37–1.74), respectively. Physiologically‐based pharmacokinetic modeling of CP‐I plasma exposure following a single dose of KHKi predicted in vivo OATP1B inhibition from about 13% to 70% over the 100 to 600 mg dose range, while using the in vitro inhibition potency (1.9 µM). Model‐based analysis correctly predicted "no‐effect" (AUC ratio < 1.25) at the low dose range and "weak" effect (AUC ratio < 2) on atorvastatin pharmacokinetics at the high dose range of KHKi. This study exemplified the utility of biomarker‐informed model‐based approach in discerning even small effects on OATP1B activity in vivo, and to project DDI risk at the clinically relevant doses.